Agile Leadership, Organizational Values, And Employee Performance In The Digital Era: Evidence From Indonesia’s ICT Industry - Deny Marfriady; Mafizatun Nurhayati; Rini Dwiyani Hadiwidjaja (UNIVED Press, 2026)
This study aims to analyze the effect of organizational values and agile leadership on employee performance and to test the role of digital technology transformation as a mediating variable at PT. Tekno ABC. The study applies an explanatory quantitative approach by distributing questionnaires to 290 employees using a convenience sampling technique. The data were analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results indicate that organizational values have a positive and significant effect on both employee performance and digital technology transformation. Agile leadership also has a positive and significant effect on employee performance as well as on digital technology transformation. Furthermore, digital technology transformation is proven to have a positive and significant effect on employee performance. In addition, digital technology transformation significantly mediates the effect of organizational values on employee performance as well as the effect of agile leadership on employee performance. The conclusion of this study shows that improvements in employee performance are not only directly determined by organizational values and agile leadership, but are also reinforced through an indirect pathway with digital technology transformation as a mediator.